Screening various Yarrowia lipolytica strains for citric acid production. Issue 5 (13th June 2019) - Carsanba, Erdem; Papanikolaou, Seraphim; Fickers, Patrick; Erten, Huseyin
Abstract: Citric acid (CA) productivity by Yarrowia lipolytica dependents on strain type, carbon source, carbon to nitrogen (C/N) molar ratio as well as physicochemical conditions (pH, temperature, oxygen transfer rate, etc.). In the current study, 10 different Y . lipolytica strains were first challenged in shake‐flask culture for CA production in a glucose‐based media under nitrogen‐limited conditions. For the most promising one, strain K57, CA productivity was monitored during culture in batch bioreactor for three initial C/N molar ratio (167, 367, and 567 Cmol/Nmol). The highest CA yield (0.77 g/g glucose), titre (72.3 g/L CA), and productivity (0.04 g/g.h) were found for C/N ratio of 367. However, the highest growth rate was obtained for an initial C/N ratio of 167. From these results, Y . lipolytica strain K57 could be considered to produce CA at higher titre on glucose‐based medium in batch bioreactor than others Y . lipolytica strain reported in the literature.